Exploring local knowledge and preferences for shea (Vitellaria paradoxa) ethnovarieties in Southwest Burkina Faso through a gender and ethnic lens - Karambiri, Mawa; Elias, Marlène; Vinceti, B.; Grosse, A. (Informa UK Limited, 2017)
In Africa’s ‘shea belt’, the shea tree (Vitellaria paradoxa) plays a central role in rural livelihoods and ecosystems. Yet, it faces many threats. The aim of this study is to examine local people’s classification systems and preferences for shea ethnovarieties in Burkina Faso to support domestication efforts that respect local priorities. Work was carried out among the Bobo, Sambla, Mosse and FulBe ethnic groups in two villages in south-west Burkina Faso. Participatory characterization and ranking matrices were used with 10 groups segregated by gender and ethnicity to understand if knowledge and preferences for shea ethnovarieties vary between gender and ethnic groups. Results show a general agreement across groups about top-cited ethnovariety names, characteristics and key criteria defining the classification system. Participants identified a total of 25 shea ethnovarieties according to 11 primary fruit and nut variants. The number of ethnovarieties cited varied slightly across groups, with greater consistency across ethnicities than across gender groups. Each ethnic and gender group identified certain ethnovarieties not cited by their ethnic or gender counterparts. Two ethnovarieties – ‘small shea fruit’ and ‘big shea fruit’ – were preferred across groups. The study highlights the value of gender-sensitive participatory research for understanding local botanical knowledge and preferences.